Hybrid Renewable Energy Systems in Türkiye: A Multi-Scenario Assessment of Demand, Metering, and Carbon Tax Policies - Terkes, Musa; Mehmet Toprak, Kaan; Demirci, Alpaslan; Gokalp, Erdin; Cali, Umit (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
The accelerating demand for low-carbon energy solutions highlights the critical role of hybrid renewable energy systems (HRES) in achieving decarbonization, energy security, and economic resilience. This study offers a comprehensive techno-economic and environmental evaluation of HRES integrating photovoltaic, wind, and battery storage technologies across T & uuml;rkiye's diverse climatic regions and sectoral demand profiles (residential, commercial, industrial). Utilizing 48 scenario-based simulations via HOMER Pro, the analysis incorporates real-world policy instruments including carbon taxation, net metering (NM), and net billing (NB). A novel sensitivity analysis reveals that under NB, battery integration becomes economically viable at carbon prices above 40-50 $/tCO2,while NM lowers this threshold to around 20$/tCO(2). Additionally, a 40 $/tCO(2) carbon tax increases the renewable energy fraction by 32% and reduces the levelized cost of energy (LCOE) by 11.75%. Commercial users in wind-rich regions benefit most under NM, achieving up to 22% lower net present cost (NPC). While NM maximizes renewable deployment and short-term returns, NB ensures greater economic discipline and supports battery investments under high tariff and carbon scenarios. Expanded performance indicators, including self-supply rate, self-consumption rate, and energy exchange rate, provide operational insights beyond conventional metrics. The findings offer region-specific and policy-aware recommendations, suggesting that hybrid models combining NM and NB, supported by moderate carbon pricing and targeted incentives, can optimize system performance while ensuring affordability and equity in T & uuml;rkiye's energy transition. This framework offers strategic guidance for regulators, investors, and planners in emerging economies.
Keywords: Renewable energy sources; Carbon tax; Costs; Batteries; Investment; Optimization; Electricity; Carbon; US Department of Defense; Temperature; economic policies; hybrid renewable energy systems; net metering; net billing; techno-economic analysis; incentive mechanisms; PHOTOVOLTAIC SYSTEM; ECONOMIC-ANALYSIS; IMPACT; MANAGEMENT; Computer Science; Engineering; Telecommunications